2017
DOI: 10.1080/03091929.2016.1275609
|View full text |Cite
|
Sign up to set email alerts
|

Piecewise uniform potential vorticity pancake shielded vortices

Abstract: Shielded vortices consist of a core of potential vorticity of a given sign surrounded (or shielded) by a layer of opposite-signed potential vorticity. Such vortices have specific properties and have been the focus of numerous studies, first in two dimensional geometries (where potential vorticity is just the vertical component of the vorticity vector) and in geophysical applications (mostly in layered models). The present paper focuses on three-dimensional, spheroidal shielded vortices. In particular, we focus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 41 publications
0
8
0
Order By: Relevance
“…We introduce a solid free-slip wall condition at the surface where the vortex intensity is maximum in order to mimic the flat ocean surface. This specific boundary condition is relevant only for surface eddies, and we exclude from the scope of our investigation intrathermocline eddies or meddies as considered by Nguyen et al (2012), Hua et al (2013), Yim et al (2016), Facchini and Le Bars (2016), Sutyrin and Radko (2017), Reinaud (2017), and Mahdinia et al (2017). Unlike these previous studies dedicated only to Gaussian lenses, we will study various radial and vertical profiles in order to extract some general stability properties which are not profile dependent.…”
Section: Introductionmentioning
confidence: 99%
“…We introduce a solid free-slip wall condition at the surface where the vortex intensity is maximum in order to mimic the flat ocean surface. This specific boundary condition is relevant only for surface eddies, and we exclude from the scope of our investigation intrathermocline eddies or meddies as considered by Nguyen et al (2012), Hua et al (2013), Yim et al (2016), Facchini and Le Bars (2016), Sutyrin and Radko (2017), Reinaud (2017), and Mahdinia et al (2017). Unlike these previous studies dedicated only to Gaussian lenses, we will study various radial and vertical profiles in order to extract some general stability properties which are not profile dependent.…”
Section: Introductionmentioning
confidence: 99%
“…The second natural extension is to consider the ageostrophic effects, by studying the interaction at small yet finite Rossby number. Recent studies by Ciani et al (2016), Reinaud andDritschel (2018) andOrozco Extrada et al (2020) have shown that these effects can drastically alter the interaction between two vortices, and in particular the way they merge. Notably cyclonic and anticyclonic vortices have asymmetric dynamical behaviours.…”
Section: Discussionmentioning
confidence: 99%
“…Richardson et al 2000). The stability of various baroclinic eddies has been studied by many authors, including Nguyen et al (2012), Meunier et al (2015), Yim et al (2016), Storer et al (2018), Menesguen et al (2018), Meunier et al (2018), Carton et al (2014) for so-called Gaussian vortices, or for piecewise uniform vortices by Miyazaki et al (2003), Reinaud (2017). On the other hand, tripolar vortices where two likesigned vortices are at the same depth have been investigated by Reinaud and Carton (2015).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Journal of Geophysical Research: Oceans 10.1002/2017JC013610 shielded eddy has a core of vorticity of one sign surrounded (or shielded) by a layer of smaller eddies of opposite-signed vorticity. This type of vortex has been studied in a theoretical and idealized setup (see e.g., Carton, 1992;Flierl, 1988;Reinaud, 2017). The discovery of shielded eddies in the real ocean is a result deserving special consideration.…”
Section: Comparison Of Hydrographic Cross Sections During May 2004mentioning
confidence: 99%